APAKAH KOMPOSISI DEWAN DIREKSI DAN DEWAN KOMISARIS MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR)? - Rizky Eriandani; Christarina Kuswanto (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2016)
Abstract: Research is intended to determine whether the composition of the board (board of directors and board of commissioners), which consists of the presence of women councils, boards of foreigners, and the proportion of independent commissioners, have an effect on the disclosure of the activities of Corporate Social Responsibility (CSR) in the annual report. This study uses a quantitative approach using multiple linear regression method. The sample used in this study are all companies listed on the Stock Exchange in the period 2010-2012, a total of 795 firm- years. The control variables used are company size, profitability and debt to equity. These results indicate that the composition of the board and the control variables simultaneosly affect CSR,  the presence of women council and the existence of  foreign  boards, on boards of directors and commissioners, as well as the size of the company's positive significant effect on the disclosure of CSR. However, the proportion of independent commissioners, profitability, and the ratio of debt to equity has no significant effect on the disclosure of CSR. Keywords: Corporate Social Responsibility Disclosure, Board Diversity, Board of Women, Foreign Board, The Proportion of Independent Board